Peran Metode Pembelajaran Dalam Meningkatkan Minat Belajar Siswa Pada Mata Pelajaran Pendidikan Agama Islam - Afifatun, Siti; Fitriana, Anisa; Ansori, Afifah (Ar-Rusyd: Jurnal Pendidikan Agama Islam, 2025)
The learning method in a lesson is certainly needed so that educators can better understand students and differences in learning styles that students have, so it will make it easier for educators to adjust strategies or methods in delivering lesson content. This study itself uses a qualitative approach that applies the literature study method. The purpose of literature study or literature study is to find a theoretical basis or literature review that is in accordance with the problems discussed and used as a reference in the elaboration of research results. In this case, of course, the role of teachers as educators is very important to find the right method in building student interest in learning. So that the creation of appropriate learning objectives of educators.